Enhancing mechanical properties of thermoplastic polyurethane elastomers with 1,3-trimethylene carbonate, epsilon-caprolactone and L-lactide copolymers via soft segment crystallization (eXPRESS Polymer Letters, 2011)
Multiblock thermoplastic polyurethane elastomers based on random and triblock copolymers were synthesized and studied. Dihydroxyl-terminated random copolymers were prepared by ring opening copolymerization of ε-caprolactone (CL) and 1,3-trimethylene carbonate (TMC). The triblock copolymers were synthesized by using these random copolymers as macro-initiator for the L-lactide (L-LA) blocks. These random and triblock copolymers were further reacted with 1,6-hexamethylene diisocyanate (HMDI) and chain extended by 1,4-butanediol (BDO). The polymer structure and chemical composition were characterized by 1H NMR 13C NMR and SEC. Their thermal and mechanical properties were studied by using DSC and Instron microtester. Multiblock polyurethanes based on random PCL-co-PTMC copolymers showed strain recovery improvement with increasing PCL content. However, these polyurethanes were unable to sustain deformation at body temperature due to the melting of PCL crystals and low hard segments content. With the presence of crystallizable PLLA blocks, mechanical properties were improved at body temperature without compromising their good strain recovery.